PENGARUH BAURAN ECERAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA BUTIK BATIK TRUSMI DI CIREBON - Rizki Zulfikar; Arionita Chasti (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
Retailing Mix is one of the factors that influence consumer purchase decisions on retailing. One of the important strategy in retailing is to know what the factors that influences consumer purchasing decisions while buying a product. This study research used to obtain an overall picture of the execution on retailing mix at Butik Batik Trusmi while the goal is to know how size and how much influence of consumer purchasing decisions at Butik Batik Trusmi in Cirebon. To answer this research, descriptive analysis and verification by quantitative analysis had done, and the data used of preparation in this thesis was obtained by conducting interviews, observations, surveys, and distribution of questionnaires. And the software to analyzed data was using SPSS 15 For Windows. While the sample had 50 people next hypothesis test results revealed the existence of significant influence of r = 0.812 between the retailing mix and consumer purchasing decisions proved by obtaining thitung was 9,70 and greater than ttable = 2,011. Based on the research found that the magnitude of the role on retailing mix to the consumer purchasing decisions at Butik Batik Trusmi in Cirebon is 65,93% and the balance of 34,07% is the influence of other factors that the authors neglected in this research. In a total score of respondents retailing mix has a score value 81,17, the value is included in both categories while the consumer purchasing decision is fair and can be seen from the percentage of the total score indicating a relatively good value that is equal to 82,10. Keyword: Retailing Mix, Consumer Purchasing Decisions